Eksplorasi Corporate Social Responsibility (CSR) Aplikasinya pada Industri Pariwisata di Ubud, Bali - Ida Ayu Putri Widawati (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2021)
This study explores how to apply Corporate Social Responsibility (CSR) to the tourism industry, especially the Travel agencys in Ubud Gianyar. Is it in line with the concept of environmentally friendly travel? The implementation of CSR can be done by building stages, such as an understanding of mature in the implementation of CSR where based on understanding and practice CSR is carried out in accordance with 5 stages in organizational learning, namely the defensive, compliance, managerial, and strategic stages. This study used a qualitative approach. Data were collected through in-depth interviews with the company. From the seventeen existing travel agencies, eight travel agencies were interviewed. Most of the Travel agencys in Ubud are still at the reactive level, namely responding by providing support for stakeholder activities, although some of them have been proactive and active. The practice of CSR is only in the defensive and compliance stages, namely the building stage, such as building an image in the community. Only a few are already at the managerial and strategic level.